Community-centered instrumentation and monitoring of nature-based solutions for urban stormwater control - O’Brien, Colleen M.; Mossman, Malcolm; Chamberlain, Lucas; Jenkins, Jennifer; Watson, John; Wilson, Ryan; Williams-Clark, Drew; Singer, Alec; Riggio, Kara; Gallet, Danielle; Miller, William M.; Packman, Aaron I. (Frontiers in Water, 2024)
Climate change is increasing the frequency and severity of extreme precipitation events, requiring new ways of managing stormwater, particularly in urban areas. Nature-based solutions (NBS) have become increasingly popular to provide distributed stormwater storage while supporting urban biodiversity and access to nature. However, long-term monitoring of the hydrological performance of NBS is limited. To date most literature has focused on monitoring methodologies for specific sites and types of NBS, use of remote sensing and modeling for large-scale assessments, or measuring benefits of NBS for urban heat mitigation. More comprehensive and consistent measurement strategies are needed to understand the effects of distributed NBS on urban hydrology at the regional scale, and improve the design, maintenance, and adoption for community-centered stormwater management. To address these gaps, we review available literature on measurement methods, summarize these methods and provide specific recommendations for instrumentation and in situ monitoring of common types and scales of urban NBS. Based on our findings on performance monitoring for individual NBS sites, we extend recommendations for consistent hydrological assessment of distributed NBS at regional scale and the efficacy of NBS in reducing community flooding impacts. These recommendations are particularly applicable for municipalities, researchers and community-based organizations who are now leading the planning and implementation of community-centered NBS systems in many areas.